The correlation and predictive value of Hb, RDW and their association for short-term and long-term mortality in patients with acute aortic dissection - Hou, Peng; Xia, Lin; Xin, Fangran; Sun, Boxuan; Zhang, Guoxin; Yu, Liming; Wang, Huishan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study examines the relationship between Hb, RDW and their association and both short-term and long-term mortality in patients with acute aortic dissection (AAD), aiming to establish combined effect between Hb and RDW as a potential prognostic biomarker for AAD outcomes.MethodsWe extracted clinical data from the Medical Information Mart for Intensive Care (MIMIC) databases for this analysis. Using adjusted Cox regression and Kaplan-Meier survival curve analyses, we assessed the relationship between Hb, RDW and their association at admission and mortality at multiple post-discharge intervals (30 days, 90 days, 1 year, and 5 years) among patients with AAD. Additionally, subgroup analyses and receiver operating characteristic (ROC) curve analyses were conducted to evaluate the predictive accuracy of Hb, RDW and their association for mortality in this patient population.ResultsHigh RDW combined with low Hb (RDW ≥ 13.60 and Hb < 7.9) significantly predicted increased mortality at 30 days, 90 days, 1 year, and 5 years post-diagnosis, with hazard ratios (HRs) as follows: 4.33 (95% CI: 1.82–10.33, P < 0.001), 4.48 (95% CI: 2.06–9.77, P < 0.001), 3.38 (95% CI: 1.70–6.70, P < 0.001), and 3.07 (95% CI: 1.66–5.66, P < 0.001), respectively.ConclusionHb and RDW are both abnormal (Hb with low level, RDW with high level) is positively correlated with 30 days, 90 days, 1 year, and 5 years mortality risk in patients with AAD. This suggests that combined effect between Hb and RDW is a significant predictor of short-term to long-term mortality risk in this patient population, highlighting its potential utility as a prognostic marker in clinical settings.